Pengaruh Modal Minimal Investasi, Pemahaman Investasi dan Motivasi Investasi Terhadap Minat Investasi Mahasiswa di Pasar Modal - Kholilullah, Muhammad Taufan; Sutarni, Sutarni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to determine the influence of minimum investment capital, investment understanding, and investment motivation on interest in investing in the capital market (case study of students at Amikom University, Yogyakarta). The type of research used is quantitative research. The population in this study were all active students at Amikom Yogyakarta University. The sampling technique in this study used accidental sampling. The total sample was 155 respondents. Data analysis using Multiple Linear Regression. Data was collected through questionnaires. The partial research results of minimum investment capital and investment motivation have a positive and significant effect on students' interest in investing in the capital market. Meanwhile, understanding has an insignificant positive effect on students' interest in investing in the capital market. Simultaneously, minimum investment capital, investment understanding, and investment motivation have a significant effect on students' investment interest in investing in the capital market.